THE DETERMINATION OF THE RHEOLOGICAL OPTIMUM OF OPHTHALMIC GELS. MODERN ASPECTS OF THE OPHTHALMIC DOSAGE FORMS DEVELOPMENT - M. N. Anurova; E. O. Bakhrushina; I. V. Lapik; S. P. Krechetov (Разработка и регистрация лекарственных средств)
The article describes the main requirements for ophthalmic gels and presents the study of the rheological properties of ophthalmic gels, registered in the Russian Federation: Korneregel®, Solcoseryl®, Vidisic®, Ophtagel®, Oftan-Timogel®, Systein gel®. The parameters of rheological measurements conducted for ophthalmic gels are substantiated. On the basis of the results obtained, optimum rheological characteristics are suggested, which can be recommended for use in the development of ophthalmic gels.